Enhanced Photocatalytic Activity of Bi3NbO7 by Fabrication of CuBi2O4/Bi3NbO7 Heterojunction Photocatalyst - Zhenkun Cheng; Dongbin Liu; Lihui Fan; Yanming Shen (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Bi3NbO7 has been widely studied as a bismuth-based photocatalyst for degradation of organic pollutants. However, the fast recombination of photo-excited carriers limits its photocatalytic performance. In this work, the CuBi2O4/Bi3NbO7 heterojunction was successfully fabricated, and its photocatalytic performance was evaluated by degradation of TC under stimulated sunlight. The optimal TC degradation efficiency of 85% was obtained on CuBi2O4/Bi3NbO7 heterojunction with CuBi2O4 mass ratio of 10% at the condition as initial TC concentration of 40 mg/L and photocatalyst dosage of 1 g/L. This optimal TC degradation efficiency is greatly higher than that of bulk Bi3NbO7 with the reaction rate constant reached 0.035 min-1 which is 3.7 times as that of Bi3NbO7. The photocatalytic degradation mechanism that based on type-II heterojunction was proposed. This work provided a promising strategy to design highly efficient photocatalysts for environmental remediation. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).